Synthesis and Characterization of Mixed Ligand Complexes Contain Curcumin, Schiff Base and Azide (N3‾) with Some Metal ions and Evaluation their Antibacterial Activity - Sagid M. Lateef (Journal of Global Pharma Technology, 2018)
The research included the synthesis and characterization of new Schiff Base (L3) by reaction 2-aminopyridine and isatin , also included synthesis and characterization of mixed Ligand complexes using curcumin (essential